Care & advocacy : narratives from a school for immigrant youth - Bennett, Jo (Educational leadership for social justice., 2012)
This is a book of oral narratives, collected from participants at a school created for first-generation, immigrant youth. The narrations from the students, teachers, administration, professional staff, and support personnel document the power of caring relationships in an educational setting.The narratives underscore the importance of teachers, students, and staff working together and their stories are relevant for any school setting. It turns out that teachers and students both have a need, even a longing, for connection.The narratives bring Nel Noddings' Care Theory to life and show how this theory can be practiced both inside and outside the classroom to bring about a school-wide change in culture. From the receptionist to the principal; from the the social worker to the teacher, the study shows that the daily interactions are as important as the academics in the school setting to improve inequities. Social justice takes on a new meaning, with this focus on social exchanges and personal well-being.The book can benefit those in the field as well as in teacher and leadership preparation programs; those wanting to conduct research with vulnerable populations can also benefit from this study.